Refusal of prescribed drug therapy (absolute non-adherence) after acute myocardial infarction/unstable angina: data from prospective observation in the LIS-3 registry - S. Yu. Martsevich; N. P. Zolotareva; A. V. Zagrebelnyy; N. P. Kutishenko; Yu. V. Lukina; M. L. Ginzburg; O. M. Drapkina (Столичная издательская компания, 2023)
Aim. Within the LIS-3 register of acute coronary syndrome (ACS), to evaluate the phenomenon of complete refusal of treatment (absolute non-adherence) after discharge from the hospital of patients diagnosed with acute myocardial infarction (AMI)/unstable angina (UA): to study the characteristics of absolutely nonadherent patients, disease outcomes after 2.5 years after first contact.Material and methods. The study was conducted within the framework of the LIS-3 register. This part of the study included patients who survived ACS and were discharged from the hospital in the first 9 months of 2014 (104 people) and patients who survived ACS and were discharged from the hospital in the first 9 months of 2018 (223 people). Of the 327 patients who survived after AMI/UA, 226 patients remained alive by the time of the first survey (on average 3 years after discharge). The created questionnaire was used, which includes questions about possible long-term outcomes, adherence to visits to medical and preventive institutions (health facilities) and adherence to drug therapy. 221 people answered questions about treatment, 11 (5%) of them did not take any drug therapy (absolutely non-adherent). On average, 29 months (2.5 years) after the initial survey, a repeat survey of completely non-adherent patients or their relatives was carried out, information was collected on the vital status of these patients, repeated cardiovascular events and on the use of recommended drug therapy, about visiting a health facility.Results. When comparing the clinical and demographic characteristics of patients who were adherent and completely non-adherent to the prescribed therapy, no significant differences were noted. By the time of the repeat survey, 4 patients from among those who were completely non-adherent had died, 2 had suffered ACS. Of the 6 patients who survived, at the time of re-contact, 2 had not started taking medications, explaining that they were feeling well, 2 had resumed taking medications in full, 2 - partially, contact with 1 patient was lost.Conclusion. A certain proportion of patients who have suffered AMI/UA completely refuse the prescribed treatment, mainly because they feel well. The likelihood of death and recurrent cardiovascular events in such patients is extremely high.